Fomo Vs Jomo: Understanding The Psychology Behind Social Media Consumption Behavior And Its Impact On Mental Well-Being With A Communication Psychology Approach - Arfan Maulana Hafizh; Fajar Hidayat; Amril Suansyah; M. Reza Saputra (World Journal of Islamic Learning and Teaching, 2024)
In this digital era, social media has become an integral part of people's lives, offering opportunities for connection and self-expression. However, excessive use of social media can have a negative impact on mental health, giving rise to the phenomena of FOMO (Fear of Missing Out) and JOMO (Joy of Missing Out). FOMO describes the anxiety and fear of being left behind by the latest information or trends, which can trigger anxiety and depression. In contrast, JOMO is the happy feeling of being free from the stress of social media, which increases happiness and mental well-being. This research analyzes the psychological factors underlying FOMO and JOMO, as well as their impact on mental well-being, through a communication psychology approach. The method used is literature study and in-depth interviews to collect empirical data. The results showed that FOMO increased anxiety and depression, while JOMO increased happiness and gratitude. Strategies to reduce FOMO and promote JOMO involve limiting time on social media use and practicing mindfulness.